Exploring the Use of Media in Teaching Indonesian Language Subject in Elementary School - Manan, Eka Vebri Kurniawati ‘Abd; Hairida, Hairida (LPPM STKIP Kusuma Negara, 2025)
The use of learning media plays a crucial role in improving the effectiveness of Indonesian language instruction in elementary schools. This study aims to explore the application of various learning media in teaching Indonesian language subject at the elementary level, along with the challenges faced by teachers. The research employs a qualitative descriptive approach, involving elementary school teachers as subjects. Data were collected through observation, interviews, and document analysis, and analyzed using thematic analysis. The findings indicate that the media used by the elementary teachers are audio, video and audiovisual media. However, several challenges were identified, including limited access to technology, lack of teacher training, and inadequate learning materials. Addressing these issues requires improved teacher competency, sufficient technological infrastructure, and better curriculum integration. The study highlights the importance of selecting appropriate media to support language skills development of students.